Numerical simulation on composite properties - Lee, Yan Xian. (2009)
Composites, which consist of two or more separate materials combined in a structural unit, are made from various combinations of different materials. The composite properties are governed by the characteristics of the local materials and their micro-structures. . Since composite is the most important material in structural field, there is a strong desire for new composite materials to be developed with improved properties to obtain longer span lengths and longer lifetimes.